Hex education : a novel - Kilmer, Maureen (G. P. Putnam's Sons, 2023)
"On the outside, luxury realtor Sarah Nelson looks like every other mom in the neighborhood. But she has an edge that others don't: She's a witch. And no one knows . . . except her estranged ex-coven and college friends, Katrina and Alicia. One terrible night during their freshman year, the trio accidentally burned down their dorm, and soon after they scattered. Their secret had been safe, until Sarah learns they've been invited back to commemorate the anniversary of the fire. Suddenly, the magic doesn't want to be controlled. Sarah's orange tabby cat, Katy Purry, now argues with her. Her broom has become self-brooming, and her fridge somehow restocks thirty pounds of sliced turkey for school lunches. As it grows increasingly difficult to hide the magic and the past, Sarah, Katrina, and Alicia must harness their power together to keep their secrets safe . . . before they find out if polite society still burns witches" --